2016
DOI: 10.1080/02680939.2016.1193901
|View full text |Cite
|
Sign up to set email alerts
|

High stakes testing and teacher access to professional opportunities: lessons from Indonesia

Abstract: High-stakes testing regimes, in which schools are judged on their capacity to attain high student results in national tests, are becoming common in both developed and developing nations, including the United States, Britain and Australia. However, while there has been substantial investigation around the impact of high-stakes testing on curriculum and pedagogy, there has been very little research looking at the impact on teachers' professional opportunities. The current project used a case study approach to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
0
29
0
1
Order By: Relevance
“…They believe other teachers do not have such a special status as they do. Ashadi and Rice (2016) found that teachers who taught NE-tested subjects are believed to gain more access to professional education. It is not uncommon that an English teacher is mandated to teach students sitting in the final year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They believe other teachers do not have such a special status as they do. Ashadi and Rice (2016) found that teachers who taught NE-tested subjects are believed to gain more access to professional education. It is not uncommon that an English teacher is mandated to teach students sitting in the final year.…”
Section: Discussionmentioning
confidence: 99%
“…They tend to neglect the other materials that are beyond the simulation tests of NE. Ashadi and Rice (2016) found that teachers see NE as the breeding ground of discrimination on teacher professionalism development. Effendi and Suyudi (2017) revealed that teachers believed that they are confined in a comfort zone as they have to repeat the same materials every year, making them demotivated to improve their teaching strategies.…”
mentioning
confidence: 99%
“…Based on the research related to the DIF study for a number of dichotomy items, it can be concluded that (1). the study of the effects of DIF can be classified according to various factors, including gender, race, test difficulties, distribution of test participant abilities, sample size, length of test and many tests infected DIF; (2). commonly used methods comparing the efficacy of different methods of DIF (using CTT and IRT analysis) are: MH method and Logistic Regression, used to compare power tests and level type I errors as shown by the research of Hidalgo and Lopez-Pina and Moses, Miao, and Dorans and Vaughn and Wang [34].…”
Section: Dif Detection Methodsmentioning
confidence: 99%
“…The are three DIF detection methods used in this study: (1). IRT-Likelihood ratio (IRT-LR), (2). Mantel-Haenszel (MH), and (3).…”
Section: B Dif Detection Methodsmentioning
confidence: 99%
“…A number of studies have been devoted to address teacher professionalism issues as well as TPD programs aiming at enhancing teachers' professionalism [21,22,23]. TPD programs in Indonesia which focuses on improving four areas of teacher competencies: pedagogical, professional, personality, and social competences, have been developed intensively along with the implementation of teacher certification programs, Teacher Profession Education (PPG), as well as other forms of teacher training programs conducted by local governments or appointed training institutions.…”
Section: St Teachers Iqf and Tpd Programsmentioning
confidence: 99%